Curriculum Management in the Political Education Program of Islamic Political Parties: An Analysis of the PKS Party Training System - Kusnan Imran (Yayasan Adra Karima Hubbi, 2025)
Background. Curriculum management in political training (DIKLAT) plays a crucial role in sustaining ideological orientation and leadership regeneration within political parties. In the context of Islamic political parties in Indonesia, particularly Partai Keadilan Sejahtera (PKS), the curriculum must align with the mandates of the Party Law and Government Regulations to ensure consistent cadre development. Purpose. This study aims to analyze the planning, implementation, and evaluation of the PKS political training curriculum. It further seeks to understand the implications of such a structured and tiered curriculum on cadre competency, ideological resilience, and leadership preparedness. Method. A qualitative descriptive method was employed by analyzing official documents and conducting interviews with key organizational stakeholders responsible for political education within PKS. Data were interpreted through thematic content analysis. Results. The findings show that PKS employs a structured curriculum through three main programs: coaching, training, and education. The implementation is conducted in stages—weekly and monthly—while evaluation follows a continuous monitoring and feedback model. This systematic approach supports the quality and sustainability of member development. Conclusion. The structured and evaluative nature of the PKS curriculum reflects a strategic effort to maintain ideological integrity and leadership quality. Future improvements are suggested through optimizing coaching techniques, reinforcing practical training modules, adopting merit-based progression systems, and strengthening internal feedback mechanisms.